The Superiority Of Micro-Algae As A Potential Feedstock For Alternative Energy - M Udiharto; Rino Nirwawan; Sri Astuti Rahayu (Testing Center for Oil and Gas LEMIGAS, 2009)
Micro-algae are plant like organisms belong to Thallophytic group, they have no true roots, stems, and leaves. They can easy to grow in fresh, saline, and brackish water. Like plants, micro-algae can conduct photosynthetic process to manufacture carbohydrates for their own food. Algal cell generally contains high concentration of proteins, carbohydrates, and lipids. Micro-algae grow very rapidly, and their biomass is commonly double within 24 hours. The algal are the highest potential energy yield agricultural oil crop. In accordance with capability of their lives, micro-algae have potential as feedstuff for alternative energy. Other capabilities of algal are as carbon dioxide reduction, animal feed, livestock feed, fertilizer, supplement for human health, etc.